Keterampilan Menulis Karangan Narasi pada Anak Gifted with Disynchronous Development (Studi Tunggal pada Satu Subjek): Narrative Writing Skills in Children Gifted with Disynchronous Development (Single Study on One Subject) - Wachidah, Kemil (Pedagogia : Jurnal Pendidikan, 2017)
This case study described twelve narrative essays of Miko within aspects of language, cognitive, and affective. Miko is Gifted child With Disynchronous Development. The results indicated that the narrative essays in aspects of language, cognitive, and affective, as follows: 1) organizing content according to the narrative structure that consists of five components, namely opening, inciting moment, development stage, denouement and ending; 2) choice of words (diction) that appear in the narrative essays are general and specific words, abstract, slang, foreign, and a figure of speech metaphor; 3) the sentences that appear in the narrative essays are simple sentence, compound sentence, and complex sentence; 4) tools of cohesion grammatical in the narrative essays are reference, substitution, ellipsis, and conjunction; and 5) specific style of spelling was found consistently in the narrative essays; 6) cognitive skill of Miko in the narrative essays is inference; and 7) affective skill of Miko are openness, sympathetic, gracious, and emphathetic in the narrative essays.